2008
DOI: 10.1186/1744-859x-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole augmentation in poor insight obsessive-compulsive disorder: a case report

Abstract: BackgroundObsessive-compulsive disorder is associated with a relevant impairment in social and interpersonal functioning and severe disability. This seems to be particularly true for the poor insight subtype, characterised by a lack of consciousness of illness and, consequently, compliance with treatment. Poor responsiveness to serotonergic drugs in poor insight obsessive-compulsive patients may also require an augmentation therapy with atypical antipsychotics.MethodsWe reviewed a case in which a patient with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(12 reference statements)
0
8
0
2
Order By: Relevance
“…Studies investigating atypical antipsychotic augmentation among adults indicated a moderate response rate, ranging from 33% to 50% (17). Aripiprazole augmentation in treatment-resistant OCD patients was already mentioned in some reports (17,(18)(19)(20). Aripiprazole, a third line atypical antipsychotic, has D2 receptor antagonism in dopaminergic hyperactivity states, and has partial receptor agonism in dopaminergic hypoactivitiy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies investigating atypical antipsychotic augmentation among adults indicated a moderate response rate, ranging from 33% to 50% (17). Aripiprazole augmentation in treatment-resistant OCD patients was already mentioned in some reports (17,(18)(19)(20). Aripiprazole, a third line atypical antipsychotic, has D2 receptor antagonism in dopaminergic hyperactivity states, and has partial receptor agonism in dopaminergic hypoactivitiy.…”
Section: Discussionmentioning
confidence: 94%
“…Due to imbalance between dopamine and serotonergic pathways in OCD neurobiology, effect of aripiprazole may be explained with its partial agonistic activity on D2, and 5 HT1A receptors, as well as antagonistic activity on 5HT2A receptors (26,30,31). Aripiprazole may be administered as monotherapy or as a combination treatment with SSRIs (17,19,24,25). In a case report of treatmentresistant OCD which was prescribed clomipramine (150mg/day) augmented with aripiprazole (12.5mg/ day), it was reported that augmentation with high dose aripiprazole improved patient symptoms markedly rather than augmentation with risperidone or quetiapine after administration of clomipramine in adequate dose and period.…”
Section: Discussionmentioning
confidence: 99%
“…Aripiprazole monotherapy has also been reported [ 61 , 62 ]. Successful use of aripiprazole in OCD with poor insight or with delusion may be of clinical interest, as aripiprazole is an SGA that would be indicated for psychotic disorders [ 48 , 56 ].…”
Section: Obsessive–compulsive Disorder (Ocd)mentioning
confidence: 99%
“…Farmakolojik profili açisindan D2 ve 5-HT1A reseptörlerine parsiyel agonist, 5-HT2A reseptörleri için ise antagonist etkilidir (13). Dopaminerjik ve serotonerjik sistemler üzerine bu karma §ik ve kendine özgü etkileri açisindan OKB hastalannda tek ba §ina ya da SSRI'Iarla birlikte kullanilabilecegi dü §ünülmektedir (14)(15)(16)(17). Da Rocha ve Correa (2007), kiomipiramin tedavisine dirençli ve olanzapin ve risperidon ile birlikte kullanildigmda yine yanit vermeyen bir OKB hastasinda aripiprazol (7,5 mg/g) ile kiomipraminin ba §anli oldugu bir olgudan bahsetmektedir (18).…”
Section: Giri §unclassified
“…Çah §malarda SSRI tedavisinin plaseboya olan belirgin üstünlügü kanitlanmi § olsa da hastalarda rezidüel belirtilerin tedavisinin bu ajanlarla tam olarak saglanamadigi pek cok olgu dikkati çekmektedir. Farmakolojik e § zamanli tedavi stratejileri arasmda tedaviye antipsikotik eklenmesi eri §kin hasta grubunda oldugu gibi pediatrik grupta da sik ba §vurulan bir yöntemdir (14,15). Eri §kin hastalarda antipsikotik eklenmesinin %33 ila 50 arasmda tedaviye yaniti arttirdigmi gösteren çah §malar bulunmaktadir (16).…”
unclassified